2014
DOI: 10.2105/ajph.2013.301744
|View full text |Cite
|
Sign up to set email alerts
|

A Syndemic of Psychosocial Health Disparities and Associations With Risk for Attempting Suicide Among Young Sexual Minority Men

Abstract: Interventions addressing multiple psychosocial health outcomes should be developed and tested to better meet the needs of young MSM and MSMW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
136
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(152 citation statements)
references
References 50 publications
12
136
0
4
Order By: Relevance
“…Additionally, use of clear and transparent language that more accurately defines measurements of SMU may be beneficial. Results of this review echo the findings of a body of research that found elevated prevalence of depression and psychological distress among LGB individuals compared to heterosexual counterparts [47][48][49][50]. Our findings point to the variability in experiencing depression and psychological distress in association with SMU for bisexually identified individuals.…”
Section: Discussion Principal Resultssupporting
confidence: 79%
“…Additionally, use of clear and transparent language that more accurately defines measurements of SMU may be beneficial. Results of this review echo the findings of a body of research that found elevated prevalence of depression and psychological distress among LGB individuals compared to heterosexual counterparts [47][48][49][50]. Our findings point to the variability in experiencing depression and psychological distress in association with SMU for bisexually identified individuals.…”
Section: Discussion Principal Resultssupporting
confidence: 79%
“…Some studies (Balsam and Szymanski, 2005; Carvalho et al, 2011; Finneran and Stephenson, 2014) showed the existence of a relationship between experienced discrimination and a higher risk of IPV. On the other hand, studies on the relationship between experienced discrimination and risk of SSIPV victimization are contradictory: some indicated the existence of such a relationship (Carvalho et al, 2011; Andrews et al, 2014; Finneran and Stephenson, 2014), while some denied it (Barrett and St.Pierre, 2013; Andrews et al, 2014). …”
Section: Sexual Minority Stressmentioning
confidence: 99%
“…The depression status that contributes to syphilis disparities among MSM is broadly consistent with Meyer’s minority stress model 25. This developmental model argues that early stressors associated with sexual minority status produce external and internal stress processes (eg, antigay prejudice, discrimination, internalised homophobia, expectations of rejection) that contribute to mental health and recreational drugs use disorders later in life 26. Work in China has suggested that depression is associated with lower adherence to antiretroviral drugs and also to higher stigma related to male homosexuality27; it would be important to also study these dynamics with syphilis, as a curable STI.…”
Section: Discussionmentioning
confidence: 58%